2019
DOI: 10.1182/blood-2018-06-860270
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for hereditary angioedema with normal C1 inhibitor: an inhibitory regulatory role for the factor XII heavy chain

Abstract: The plasma proteins factor XII (FXII) and prekallikrein (PK) undergo reciprocal activation to the proteases FXIIa and kallikrein by a process that is enhanced by surfaces (contact activation) and regulated by the serpin C1 inhibitor. Kallikrein cleaves high-molecular-weight kininogen (HK), releasing the vasoactive peptide bradykinin. Patients with hereditary angioedema (HAE) experience episodes of soft tissue swelling as a consequence of unregulated kallikrein activity or increased prekallikrein activation. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 55 publications
7
79
0
1
Order By: Relevance
“…importantly, no PMM2-CDG patient neither from our cohort nor from the literature has ever developed angioedema to our knowledge. These data support recent studies showing the key role of the N-terminal domain of FXII in the activation of this molecule [30]. However, we must remember that most PMM2-CDG patients have not been exposed to the triggering factors that cause angioedema in carriers of the p.Thr309Lys mutation (pregnancy, oral contraceptives…) [31], and on the other hand that marked edemas were already reported in CDG patients [32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 87%
“…importantly, no PMM2-CDG patient neither from our cohort nor from the literature has ever developed angioedema to our knowledge. These data support recent studies showing the key role of the N-terminal domain of FXII in the activation of this molecule [30]. However, we must remember that most PMM2-CDG patients have not been exposed to the triggering factors that cause angioedema in carriers of the p.Thr309Lys mutation (pregnancy, oral contraceptives…) [31], and on the other hand that marked edemas were already reported in CDG patients [32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 87%
“…This facilitates conversion of FXII protein into its active form FXIIa, which can in turn generate active kallikrein and bradykinin leading to angioedema. Ivanov et al have recently demonstrated that factor XII with Lys/Arg substitutions for Thr309 can be cleaved by thrombin and factor XIa generating the truncated species δFXII, which in turn activates kallikrein. In ANGPT1‐HAE, the mechanism of angioedema implies that this mutation could impair the interaction of angiopoietin‐1 with its endothelial membrane receptor TIE2, leading to a vascular leakage and angioedema .…”
Section: Introductionmentioning
confidence: 99%
“…FXII molecules with the variant adopt an open or relaxed conformation which facilitates the access of PKa and plasmin to their FXII-activating moieties and also exposes cryptic proteolytic targets for thrombin which are normally concealed and not accessible in the compact conformation of FXII ( de Maat and Maas, 2016 ). Moreover, the cleavage of FXII Thr 328Lys by thrombin leads to enhanced activation of the contact system and bradykinin-mediated angioedema ( Ivanov et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%